2012
DOI: 10.1093/aob/mcs263
|View full text |Cite
|
Sign up to set email alerts
|

Zinc uptake and radial transport in roots of Arabidopsis thaliana: a modelling approach to understand accumulation

Abstract: The model captures the experimental findings very well and confirms the hypothesis that low abundance of HMA4 produces a radial gradient in zinc concentration. Surprisingly, transpiration was found also to be a key parameter. The model suggests that ZIP regulation takes place on a comparable timescale as symplastic transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 53 publications
1
35
0
Order By: Relevance
“…Zn uptake into the symplast in the outer root layers and loading into the apoplastic xylem stream are well understood on molecular level (Moreira, Moraes, & dos Reis, ). However, the dynamics of symplastic movement and patterning of the radial transport have thus far only been modeled to elucidate the timescales of these events (Claus et al., ). After xylem loading, the mass flow‐mediated movement of Zn into the shoot inside the xylem is expected to occur within 30 min in Arabidopsis , as previously shown for water (Park et al., ) and Cd in xylem sap (Ueno et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Zn uptake into the symplast in the outer root layers and loading into the apoplastic xylem stream are well understood on molecular level (Moreira, Moraes, & dos Reis, ). However, the dynamics of symplastic movement and patterning of the radial transport have thus far only been modeled to elucidate the timescales of these events (Claus et al., ). After xylem loading, the mass flow‐mediated movement of Zn into the shoot inside the xylem is expected to occur within 30 min in Arabidopsis , as previously shown for water (Park et al., ) and Cd in xylem sap (Ueno et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The slower speed of Zn transport indicates that Zn loading into the xylem by HMA4 is slow and under tight control even in the metal hyperaccumulator A. halleri . Modelling the radial transport of Zn uptake has indeed indicated that HMA concentration is one of the key determinants of the uptake dynamics (Claus et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is generally accepted that the uptake of Zn from soil has at least four main mechanisms (see also Aucour et al, 2011;Caldelas et al, 2011;Houben et al, 2014;Jouvin et al, 2012;Tang et al, 2012 and references herein): (1) root-induced soil acidification and mobilization of soil Zn (Houben et al, 2014;Loosemore et al, 2004); (2) Zn adsorption on root cell wall (Hall, 2002); (3) non-specific Zn transfer through the plasma membrane into the root symplast via low-affinity transporters (Hacisalihoglu et al, 2001), or (4) Zn specific uptake by either ZIP proteins or phytosiderophores released by the plant roots to transfer the Fe/Zn complexes through the membrane (Claus et al, 2013). The present growth media are far from the Fe-or Zn-deficiency conditions, hence the release of siderophores by L. multiflorum roots was probably negligible (Rö mheld and Marschner, 1990).…”
Section: Species Differences In Zn Uptake Translocation and Isotope mentioning
confidence: 99%